2016
DOI: 10.4300/jgme-d-15-00505.1
|View full text |Cite
|
Sign up to set email alerts
|

Daily Encounter Cards—Evaluating the Quality of Documented Assessments

Abstract: Background Concerns over the quality of work-based assessment (WBA) completion has resulted in faculty development and rater training initiatives. Daily encounter cards (DECs) are a common form of WBA used in ambulatory care and shift work settings. A tool is needed to evaluate initiatives aimed at improving the quality of completion of this widely used form of WBA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…Two previous studies seeking to provide validity evidence for the CCERR found that DECs and ITERs that had been judged by experts to be of 'average' quality received mean CCERR scores of 24.2 and 23.8, respectively. 25,26 The mean CCERR scores for all three groups in our study were lower, suggesting that the quality of DECs completed by supervisors fell below a standard that would be considered to represent 'average' quality. Although this is disappointing, our results are congruent with those of other studies which demonstrate that clinical supervisors consistently fail to complete WBAs to an adequate standard, as represented by similarly low mean CCERR scores (range: [15][16][17][18][19][20][21][22].…”
Section: Quality Of Decs and Resident Performancementioning
confidence: 59%
See 2 more Smart Citations
“…Two previous studies seeking to provide validity evidence for the CCERR found that DECs and ITERs that had been judged by experts to be of 'average' quality received mean CCERR scores of 24.2 and 23.8, respectively. 25,26 The mean CCERR scores for all three groups in our study were lower, suggesting that the quality of DECs completed by supervisors fell below a standard that would be considered to represent 'average' quality. Although this is disappointing, our results are congruent with those of other studies which demonstrate that clinical supervisors consistently fail to complete WBAs to an adequate standard, as represented by similarly low mean CCERR scores (range: [15][16][17][18][19][20][21][22].…”
Section: Quality Of Decs and Resident Performancementioning
confidence: 59%
“…11,12,25 A recent study demonstrated evidence for the validity of CCERR scores when applied to DECs, including high reliability and the ability to discriminate DECs of varying quality. 26 In that study, mean CCERR scores for DECs that had been judged by experts to be of poor, average and high quality were 14.4, 24.2 and 37.3, respectively. 26…”
Section: Outcome Measurementioning
confidence: 82%
See 1 more Smart Citation
“…[9][10][11] Despite their widespread use, evidence suggests that the quality of assessments being documented on DECs is poor. 12,13 A study by Bandiera and Lendrum 11 found that DECs were subject to leniency or range restriction effects wherein supervisors provided "inflated" or overly favorable assessments leading to indiscriminate ratings. Sherbino et al 14 found that DEC items were not well understood by front-line supervisors, resulting in poor reliability and questionable validity of the scores.…”
mentioning
confidence: 99%
“…6 Paukert et al 2 noted that they had both resident and faculty evaluators, and noted that as the postgraduate year (PGY) increased, the number of evaluations decreased. POE systems using CECs have been described 4,6-8 with both the benefits seen of the CEC and immediacy of feedback being more useful to students. 7,9…”
Section: Interventionmentioning
confidence: 99%